2023
DOI: 10.1021/acssuschemeng.2c05789
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Modeling and Experimental Study of Carbonation of Alkali-Activated Slag Cements

Abstract: The present study investigates the carbonation of slags activated by NaOH, Na2SiO3, Na2CO3, and Na2SO4. The main hydrates in those activated with NaOH or Na2SiO3 were C-(N-)A-S-H, strätlingite, and MgAl-layered double hydroxide phases as observed using different experimental characterization techniques and thermodynamic modeling. The use of a Na2CO3 activator led to the formation of calcium carbonate and monocarbonate instead of strätlingite, and Na2SO4 to ettringite formation. Carbonation of the alkali-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Although Na 2 CO 3 ‐activated slags continue the previous trend decreasing pore solution conductivities by 27% ( μ DOR = 60% = 0.17 S/cm) as the slag degree of reaction increases (10%–60%), the Na 2 SO 4 ‐activated slags pore solution conductivities are increased by 40% ( μ DOR = 60% = 0.15 S/cm), see Figure 1C,D. While here we consider degrees of reaction of slag up to 60%, lower degrees of reaction of 39% and 33% have been observed for 10 wt.% Na 2 CO 3 and Na 2 SO 4 ‐activated slags at 50 days 29 . Hence, the results here remain theoretical and useful to understand the relative complexity of the pore solution chemistry between alkali‐ and salt‐activated slags.…”
Section: Pore Solution Chemistry Of Alkali‐ and Salt‐activated Slag M...mentioning
confidence: 87%
See 1 more Smart Citation
“…Although Na 2 CO 3 ‐activated slags continue the previous trend decreasing pore solution conductivities by 27% ( μ DOR = 60% = 0.17 S/cm) as the slag degree of reaction increases (10%–60%), the Na 2 SO 4 ‐activated slags pore solution conductivities are increased by 40% ( μ DOR = 60% = 0.15 S/cm), see Figure 1C,D. While here we consider degrees of reaction of slag up to 60%, lower degrees of reaction of 39% and 33% have been observed for 10 wt.% Na 2 CO 3 and Na 2 SO 4 ‐activated slags at 50 days 29 . Hence, the results here remain theoretical and useful to understand the relative complexity of the pore solution chemistry between alkali‐ and salt‐activated slags.…”
Section: Pore Solution Chemistry Of Alkali‐ and Salt‐activated Slag M...mentioning
confidence: 87%
“…While here we consider degrees of reaction of slag up to 60%, lower degrees of reaction of 39% and 33% have been observed for 10 wt.% Na 2 CO 3 and Na 2 SO 4 -activated slags at 50 days. 29 Hence, the results here remain theoretical and useful to understand the relative complexity of the pore solution chemistry between alkali-and salt-activated slags. In contrast with alkali-activated slag materials, the influence of Al 2 O 3 content of slags yields more significant differences in pore solution conductivity-for example, a difference of 7 wt.% Al 2 O 3 in the Ecocem slag composition can result in differences between 0.05 and 0.10 S/cm when analyzing Na 2 CO 3 -activated slags at 60% degree of reaction.…”
Section: 1mentioning
confidence: 90%
“…Activating solutions usually include sodium and/or potassium hydroxides or combinations of sodium/potassium silicate, sulfates, 43 or carbonate 44 . A study 45 on alkali‐activated GGBFS explored different activation solutions, such as NaOH, Na 2 SiO 3 , Na 2 CO 3 , and Na 2 SO 4 , and it was found that the slag exhibited a more extensive reaction when activated with NaOH and Na 2 SiO 3 solutions. The chemical composition of the silicate solution can be defined by the SiO 2 /M 2 O (M = Na or/and K) molar ratio and the H 2 O content.…”
Section: Introductionmentioning
confidence: 99%